1982
DOI: 10.1002/1520-6866(1990)2:1<91::aid-tcm1770020110>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity studies with 2,4,5-T on bacteria and mammalian germ cells

Abstract: The herbicide 2,4,5-T (2,4,5-trichlorophenoxyacetic acid) was evaluated for potential mutagenicity by a Salmonella/mammalian-microsome test, a dominant lethal test on female rats, and by a cytogenetic assay on spermatogonia of Chinese hamster. In the Salmonella/mammalian-microsome test on four Salmonella typhimurium strains (TA 1535, TA 100, TA 1537, and TA 98), doses of up to and including 2500 micrograms/plate did not cause any mutagenic effects. In a dominant lethal test on female rats, 8-week dietary admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Because the numbers of SCEs may vary remarkably between the individual cells within a cell culture, more cells would be necessary for any decisive interpretation of the data. The results of the present study support the earlier data which indicated that 2,4-D and MCPA do not act as agents which damage DNA directly [17][18][19][20]. Recently, however, data have accumulated which suggest that phenoxy acid herbicides may have genotoxic potential via an indirect mode of action.…”
Section: Discussionsupporting
confidence: 90%
“…Because the numbers of SCEs may vary remarkably between the individual cells within a cell culture, more cells would be necessary for any decisive interpretation of the data. The results of the present study support the earlier data which indicated that 2,4-D and MCPA do not act as agents which damage DNA directly [17][18][19][20]. Recently, however, data have accumulated which suggest that phenoxy acid herbicides may have genotoxic potential via an indirect mode of action.…”
Section: Discussionsupporting
confidence: 90%